Coeval minimum south American and maximum Antarctic last glacial maximum dust deposition: A causal link? - Coppo, Renata; Cosentino, Nicolas Juan; Torre, Gabriela; del Rio, Ian; Oliveira Sawakuchi, André; Berman, Ana Laura; Koester, Edinei; Delmonte, Barbara; Gaiero, Diego Marcelo (Quaternary Science Reviews)
Records of wind-blown mineral dust provide an excellent proxy of past atmospheric circulation, a key parameter to understanding Earth's climate changes. Dust deposition at distal sites depends on atmospheric conditions both in sink areas, along transport pathways, and close to dust sources. To disentangle the contributions of changes in these conditions to distal dust deposition, it is necessary to retrieve complementary information from geological dust archives at different distances from sources. In the Southern Hemisphere, paleo-dust recorded at proximal loess remains under-studied compared to dust recorded at medium- and long-range archives. Here, we expand previous sampling of southern South America's Pampean loess. New age models based on luminescence dating of potassium feldspar imply minimum dust mass accumulation rates during the early part of the Last Glacial Maximum (LGM) across all three sampled sites, in opposition to coeval maximum dust deposition in the East Antarctic Plateau (EAP). In turn, provenance analysis based on neodymium and strontium isotopes suggests that <5-μm loess mostly derived from the Puna-Altiplano Plateau (PAP). In EAP, unmixing of neodymium, strontium and lead isotopic signals confirms that LGM dust mostly derived from southern South America (contrasting with Holocene EAP dust records that suggest a combined dust contribution from southern South America and Australia), either from southern central-western Argentina or from a combination of Patagonia/Tierra del Fuego and southern Puna in the PAP. Our results favor this second scenario, in which the coincidence of minimum dust deposition in the Pampas and maximum deposition in the EAP during the LGM is in part associated with reduced close-to-source wet scavenging of fine-grained dust due to more local arid conditions and less frequent rainfall, allowing more vigorous long-range transport of southern Puna dust. Fil: Coppo, Renata. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico ...